THE EFFECT OF CASH MANAGEMENT SYSTEM EFFECTIVENESS AND GOVERNMENT CREDIT CARD ON FRAUD INDICATIONS THROUGH THE INTERNAL CONTROL SYSTEM - Ashari, Relcy; Anshar, Muh. Ashary; Nurdin, Maryam (International Journal of Economy, Education and Entrepreneurship (IJE3), 2025)
This research aims to empirically test and analyze the effectiveness of the Cash Management System (CMS) and the Government Credit Card (KKP) on fraud indications, while also assessing the role of internal control systems (ICS) as a mediating variable. The research was conducted across work units of the Central Bureau of Statistics (BPS) in South Sulawesi Province using a quantitative explanatory approach. Data were collected through questionnaires administered to 96 financial management officials, including Budget User Authorities, Commitment Making Officials, Payment Order Signatories, and Expenditure Treasurers. The data were analyzed using the Partial Least Squares - Structural Equation Modeling (PLS-SEM) method. The results indicate that the effectiveness of CMS and KKP significantly influences internal control systems. However, internal control systems do not have a significant effect on fraud indications and do not serve as a mediating variable. This means that the influence of CMS and KKP on fraud is direct, and not mediated through internal control systems. These findings suggest that the implementation of non-cash transactions such as CMS and KKP plays a direct role in reducing fraud risks, even though the current internal control systems are not yet sufficiently effective as an intervention mechanism. Therefore, strengthening and restructuring internal controls is necessary to enhance their role in fraud prevention. This study provides practical implications for government institutions in promoting financial transparency through digital payment systems and in reinforcing control over the use of public funds.